Pengetahuan dan Sikap Remaja Sekaa Teruna Teruni di Daerah Urban dan Sub Urban tentang Perilaku Seksual Berisiko - Moh Fairuz Abadi; Dyah Pradnyaparamita Duarsa (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Sexual risk behaviors in teenagers, could be a serious problems in health. Geographical clould be influence knowledge and attitudes. Sekaa Teruna Teruni is a Balinese youth organization, they can be found in all traditional villages.Objective: The research aim’s to find out the knowledge and attitudes of Sekaa Teruna Teruni in Urban and Sub Urban areas about risky sexual behavior.Methods: This is an cross-sectional study, respondents are 241 teenagers (15-21 years) sampling methode is consecutive, variables were measured using a questionnaire that had been tested before, analysis uses non-parametric mann whitney.Results adn Discussion:The results showed that p score for knowledge and attitudes <0.05 its means that there are significant.Conclusion: The level of knowledge and attitudes of respondents at the Urban location is higher, that because the flow of information and the organizational activities, efforts are needed to increase knowledge and attitudes especially at the Sub-Urban. Keywords: Risky sexual behavior; Sekaa Teruna Teruni.